ANALISIS DAMPAK PEMBIAYAAN MUDHARABAH PADA PERKEMBANGAN UMKM NASABAH BSI KCP LUBUK SIKAPING - Febri Fadilla Putri; Rusydi Fauzan (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Thesis with the title: "Analysis of the Impact of Mudharabah Financing on the Development of UMKM Customers of BSI KCP Lubuk Sikaping". compiled by Febri Fadilla Putri NIM 3319272. Thesis for a student of the Sharia Banking Study Program, Faculty of Islamic Economics and Business (FEBI), State Islamic University of Syeh M. Djamil Djambek Bukittinggi. The author's background in raising this title is because the author sees the problem faced by UMKM actors, namely the lack of financing in meeting capital needs so that they can develop their business, so in this case Bank Syariah Indonesia KCP Lubuk Sikaping is expected to carry out its role in helping customers meet their needs. capital through the provision of easy and fast financing. The research method used in this study is quantitative with the variable mudharabah financing (X) and the MSME development variable (Y). The data used are secondary data and primary data. The sample studied was 100 respondents, using the Slovin formula. Data collection techniques used observation techniques with instruments such as stationery to obtain data and survey techniques with research instruments using a Likert scale, the data analysis method used was (1) Research Instrument Test conducted using Validity Test, Reliability Test, (2) data analysis techniques using the Normality Test, Simple Linear Regression Analysis, t-test (partial), and the Coefficient of Determination (R Square). The results of this study conclude that Mudharabah Financing has a significant influence on the Development of UMKMs at the BSI KCP Lubuk Sikaping as evidenced by the results of a simple linear regression Y = 7.757+0.515X+ei where this figure shows a positive value. Based on the results of the t test, it is known that the significance value is 0.000, less than the value <α 0.05, then H0 is rejected and Ha is accepted. The results of the coefficient of determination (R-Square) of 43% have a weak effect because the value does not reach 50% while the remaining 57% is influenced by other variables outside this study.The purpose of this study is to learn how UMKM BSI KCP Lubuk Sikaping's funding crisis affected the company's growth. The data used are second- and first-level data. One hundred respondents were polled using the Slovin formula. Data collection methods using observational tools like writing implements for information gathering and surveying tools like the Likert scale for scientific inquiry. Simple linear regression analysis is the method used in data analysis techniques. This study's findings suggest that philanthropic giving has a significant impact on UMKM growth. At BSI KCP Lubuk Sikaping, as evidenced by the results of a straightforward linear regression analysis, Y = 7,757+0,515X+ei, where the positive numbers indicate a high value. If the significance level of the Uji t results is less than or equal to.00005, then H0 is rejected and Ha is accepted. The R-squared value from the analysis shows that only 43% of the variation in the dependent variable can be attributed to the independent variable. This value is low since the independent variable's value does not exceed 50%